USING THE METHODS OF SYSTEMS BIOLOGY FOR PREDICTING PERSPECTIVE TARGET GENES TO SELECT C3 AND C4 CEREALS FOR OXIDATIVE STRESS RESISTANCE - A. V. Doroshkov; A. V. Bobrovskikh (Вавиловский журнал генетики и селекции)
Reactive oxygen species (ROS) are some of the most damaging factors for living systems. Cells produce ROS during normal metabolism reactions, but ROS production increases under stressful conditions. Improving the antioxidant system in cultivated plants will increase their tolerance to abiotic stresses, such as salinity, drought and cold. However, the biochemical components of the system are redundant, for each reaction is catalyzed by a series of enzymes encoded by different genes. Choosing the most perspective components of this system will help speed up evaluating the optimal breeding strategy for improving abiotic stress tolerance in economically valuable plants. In the present research article, we present the results of an integrative analysis of evolution- and expressionrelated characteristics. The work was carried out on a series of genes that belong to 4 functional groups (APX, GPX, SOD and CAT) of enzymatic components of the antioxidant defense system in six species of C3 cereal plants and 3 species of C4 cereal plants. As a result, 25 groups of orthologous genes were evaluated and described. The highest gene expression level and the greatest pressure of purifying selection were found to characterize six groups. These genes were chosen for further verification and use in breeding. Because these genes undergo the most conservative evolution and have the highest level of mRNA expression, we may assume that they contribute a lot to the antioxidant system functioning of the C3 and C4 cereal plants studied. We have shown that the integration of evolutionary characteristics and expression data represents a promising approach to predict target genes for plant breeding.